The shaman's mirror : visionary art of the Huichol - MacLean, Hope, 1949- (University of Texas Press, 2012)
"Huichol Indian yarn paintings are one of the world's great Indigenous arts, sold around the world and advertised as authentic records of dreams and visions of the shamans. Using glowing colored yarns, the Huichol Indians of Mexico paint the mystical symbols of their culture--the hallucinogenic peyote cactus, the blue deer-spirit who appears to the shamans as they croon their songs around the fire in all-night ceremonies deep in the Sierra Madre mountains, and the pilgrimages to sacred sites, high in the central Mexican desert of Wirikuta. Hope MacLean provides the first comprehensive study of Huichol yarn paintings, from their origins as sacred offerings to their transformation into commercial art. Drawing on twenty years of ethnographic fieldwork, she interviews Huichol artists who have innovated important themes and styles. She compares the artists' views with those of art dealers and government officials to show how yarn painters respond to market influences while still keeping their religious beliefs. Most innovative is her exploration of what it means to say a tourist art is based on dreams and visions of the shamans. She explains what visionary experience means in Huichol culture and discusses the influence of the hallucinogenic peyote cactus on the Huichol's remarkable use of color. She uncovers a deep structure of visionary experience, rooted in Huichol concepts of soul-energy, and shows how this remarkable conception may be linked to visionary experiences as described by other Uto-Aztecan and Meso-American cultures."--Publisher